2014
DOI: 10.1614/ipsm-d-14-00002.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soil and Landscape Factors in Chinese Privet (Ligustrum sinense) Invasion in the Appalachian Piedmont

Abstract: There is a limited understanding about the ecological mechanisms that enable certain plant species to become successful invaders of natural areas. This study was conducted to determine the soil and landscape characteristics that correlate with invasion of Chinese privet (CHP), and to develop a model to predict the probability of CHP invasion in Piedmont forests. A landscape ecosystem classification (LEC) system—based on the percentage of clay in the B horizon, depth to maximum clay (cm), exposure, terrain shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Loewenstein 2005;Merriam and Feil 2002). Several studies have detected a negative relationship between L. sinense cover and tree density, possibly supporting this hypothesis (Barksdale and Anderson 2015;Hagan et al 2014;Hanula et al 2009;Wilcox and Beck 2007). Additionally, Hagan et al (2014) reported that tree basal area was lower in invaded plots (but recall the earlier discussion on invasion frameworks).…”
Section: Woody Speciesmentioning
confidence: 74%
See 4 more Smart Citations
“…Loewenstein 2005;Merriam and Feil 2002). Several studies have detected a negative relationship between L. sinense cover and tree density, possibly supporting this hypothesis (Barksdale and Anderson 2015;Hagan et al 2014;Hanula et al 2009;Wilcox and Beck 2007). Additionally, Hagan et al (2014) reported that tree basal area was lower in invaded plots (but recall the earlier discussion on invasion frameworks).…”
Section: Woody Speciesmentioning
confidence: 74%
“…Several studies have detected a negative relationship between L. sinense cover and tree density, possibly supporting this hypothesis (Barksdale and Anderson 2015;Hagan et al 2014;Hanula et al 2009;Wilcox and Beck 2007). Additionally, Hagan et al (2014) reported that tree basal area was lower in invaded plots (but recall the earlier discussion on invasion frameworks). However, Hanula et al (2009) and Greene and Blossey (2014) found no significant relationship between tree basal area and L. sinense cover, and others have found no significant relationship between L. sinense and overstory and subcanopy tree diversity (Kittel 2001;Wilcox and Beck 2007).…”
Section: Woody Speciesmentioning
confidence: 74%
See 3 more Smart Citations